2021
DOI: 10.1007/s00249-021-01575-9
|View full text |Cite
|
Sign up to set email alerts
|

Partial structure, dampened mobility, and modest impact of a His tag in the SARS-CoV-2 Nsp2 C-terminal region

Abstract: Intrinsically disordered proteins (IDPs) play essential roles in regulating physiological processes in eukaryotic cells. Many viruses use their own IDPs to “hack” these processes to deactivate host defenses and promote viral growth. Thus, viral IDPs are attractive drug targets. While IDPs are hard to study by X-ray crystallography or cryo-EM, atomic level information on their conformational preferences and dynamics can be obtained using NMR spectroscopy. SARS-CoV-2 Nsp2, whose C-terminal region (CtR) is predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…19,20 Existence of intrinsically disordered regions (IDRs) within the C-terminal region of SARS-CoV-2 NSP2 was also determined by using NMR spectroscopy. 16 We found that NSP2 of SARS-CoV-2 can be secreted into the culture supernatants of transfected cells. In addition, NSP2 protein from different coronaviruses, such as SARS-CoV-1, Middle East respiratory syndrome coronavirus (MERS-CoV), or porcine epidemic diarrhea virus (PEDV), was also secreted by the cells.…”
Section: ■ Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…19,20 Existence of intrinsically disordered regions (IDRs) within the C-terminal region of SARS-CoV-2 NSP2 was also determined by using NMR spectroscopy. 16 We found that NSP2 of SARS-CoV-2 can be secreted into the culture supernatants of transfected cells. In addition, NSP2 protein from different coronaviruses, such as SARS-CoV-1, Middle East respiratory syndrome coronavirus (MERS-CoV), or porcine epidemic diarrhea virus (PEDV), was also secreted by the cells.…”
Section: ■ Introductionmentioning
confidence: 75%
“…14,15,22 Similar to the Tat protein of HIV-1, SARS-CoV-2 NSP2 contains IDRs. [15][16][17]19,20,23 We then investigated whether the SARS-CoV-2 NSP2 protein could be secreted as a Tat protein. Expression vectors of SARS-CoV-2 NSP2, NSP5, and NSP8 were transfected into HEK293T cells.…”
Section: ■ Resultsmentioning
confidence: 99%
“… 6 The C-terminal region of the nonstructural protein Nsp2 has been predicted to be disordered. 107 Because it interacts with host proteins, which regulate translation initiation and endosome vesicle sorting, compounds that block these interactions could be valuable candidates for drug development. Although the other proteins exhibit lower disorder content, nearly all contain at least one IDR.…”
Section: Intrinsically Disordered Proteins In Sars-cov-2 Proteome And...mentioning
confidence: 99%
“…In the group of the nonstructural SARS-CoV-2 proteins, several moderately disordered proteinsNsp8, ORF6, and ORF9bhave been identified, as well . The C-terminal region of the nonstructural protein Nsp2 has been predicted to be disordered . Because it interacts with host proteins, which regulate translation initiation and endosome vesicle sorting, compounds that block these interactions could be valuable candidates for drug development.…”
Section: Intrinsically Disordered Proteins In Sars-cov-2 Proteome And...mentioning
confidence: 99%
“…nsp2 , a 638-amino-acid-residue protein, was found to interact with host-cell proteins regulating initiation of translation and endosome vesicle sorting. It is interesting that its C-terminal domain, which is disordered, plays a crucial role in these interactions [ 19 ].…”
Section: Sars-cov-2 Proteinsmentioning
confidence: 99%